Attitudes towards hearing, hearing loss, and hearing protection in university students. - Mina, Melissa; Loughran, Michael T.; Dawes, Piers (International Journal of Audiology, 2024)
Objective: Young adults are at risk for hearing loss caused by exposure to loud music. Intervention at this stage provides opportunities to support lifelong hearing protection use. This study explores attitudes related to hearing, hearing loss, and hearing protection among university students. Design: Qualitative interview design, supplemented by quantitative questionnaire data. Study sample: 18 university students, aged 18–24 years. Results: Students were uncertain about mechanisms of noise-induced hearing loss, did not feel vulnerable to permanent hearing damage from loud music, were unconvinced of hearing protection efficacy, and reported barriers to hearing protection use. Students emphasised the positive effects of loud music and reported an increased likelihood of using hearing protection were it used by peers. Music students appeared more aware of the negative effects of loud music exposure. Students reported conflicting attitudes regarding government regulation of hearing protection use. Conclusion: Young adults require education about hearing protection from multiple, credible sources and need to understand the mechanisms behind noise-induced hearing loss in a way that makes it of high personal relevance.